Inhibiting polysulfides with PDA/PEI‐functionalized separators for stable lithium‐sulfur batteries. (15th April 2021) - Pei, Cunbao; Li, Jingde; Lv, Zezhong; Wang, Huanmin; Dong, Wei; Yao, Yongyi
Summary: Lithium‐sulfur batteries are considered the most promising candidates for energy storage materials in the future, but the shuttle of polysulfides has seriously affected the development of lithium‐sulfur batteries. Because the surface morphology of the material determines its structural properties to some extent. Therefore, the surface of celgard‐2400 is structurally modified by controlling the polymerization of dopamine to further improve the performance of the separator. Utilizing the effective adsorption performance of dopamine and the interaction with PEI, an effective network structure is formed. The polydopamine and polyethyleneimine (PDA/PEI) coating forms a good physical barrier while a large amount of N, O elements and polysulfides adsorb each other, which effectively inhibits the shuttle of polysulfides. After coating, the rapid increase of the electrolyte wettability and liquid absorption rate of the separator will provide a guarantee for lithium ion transmission. Through electrochemical tests, the initial capacity of the battery modified by PDA/PEI coating reached 1250 mAh g −1 at 0.2 C, and remained above 900 mAh g −1 after 100 cycles. While the rate performance and cycle stability are improved, the electrochemical impedance is also reduced. This solution can be prepared lot size is a promising improved technology.